Augmented Reality (AR) in Education: Enhancing Learning Experiences or Distracting Novelty? - Prof.N.K.Chandra (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper explores the potential of Augmented Reality (AR) to enhance learning experiences in various subjects. It examines how AR can be used to visualize complex concepts, create immersive simulations, and increase student engagement. The research may analyze the effectiveness of AR compared to traditional learning methods, considering potential drawbacks like technical limitations and distractions.